Communication, an important link between healthcare providers: a best practice implementation project. (September 2022) - Ifrim, Raluca Alexandra; Klugarová, Jitka; Măguriță, Daniela; Zazu, Mariana; Mazilu, Doina Carmen; Klugar, Miloslav
ABSTRACT: Objectives: This project aimed to improve communication skills of medical laboratory staff and the quality of health services. Introduction: Communication is the basis of all interpersonal actions; optimal and efficient communication needs permanent awareness and training in order to learn these skills. The healthcare industry is a constantly changing field, so communication becomes a very important tool that contributes to change. Methods: This project has been conducted following the JBI framework to improve the communication process in a medical laboratory. A baseline audit involved 30 multidisciplinary healthcare providers (HCP). Using audit criteria provided by JBI, data for clinical audits were collected using a completed audit questionnaire based on direct observation and interview of participants, and checking the records. Once the information had been gathered, the team involved in the project implemented a three sessions workshop focused on communication to solve/improve identified barriers. A follow-up audit was conducted to assess the outcomes of the intervention. Results: The implementation of the project resulted in the evolution of the participants and the cohesion of the healthcare team. The baseline compliance with best practice for audit criteria shows that only a part of those involved in the study benefited from training communication. Lack of time for team briefings and interactions led to different points of view. In the pandemic context, the implementation of the communication improvement strategy was conducted online, with all 30 HCP participating in training sessions. After the follow-up audit, the evolution was demonstrated by the improvement of the HCP compliance compared with the two audit criteria identified with the insufficient compliance in the basic audit. Conclusion: Effective communication is a necessity to meet patient needs and to provide high-quality services. The healthcare team received training for communication focused on interpersonal communication.